1984
DOI: 10.1093/nar/12.8.3473
|View full text |Cite
|
Sign up to set email alerts
|

Human placental DNA methyltransferase: DNA substrate and DNA binding specificity

Abstract: We have partially purified a DNA methyltransferase from human placenta using a novel substrate for a highly sensitive assay of methylation of hemimethylated DNA. This substrate was prepared by extensive nick translation of bacteriophage XP12 DNA, which normally5 has virtually all of its cytosine residues replaced by 5-methylcytosine (m C). Micrococcus luteus DNA wgs just as good a substrate if it was first similarly nick translated with m dCTP instead of dCTP in the polymerization mixture. At different stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 55 publications
(74 reference statements)
1
23
0
Order By: Relevance
“…The procedure used for isolating MDBP and DNA methyltransferase from human placental nuclei involved previously described methods with some modifications (14,15). Two full-term placenta minus the chorionic plate were minced and homogenized for 10 sec at full speed in a Waring Blender and then in a Potter-Elvejehm homogenizer with six strokes at 3/4 maximum speed using 3-4 volumes of 50 mM Tris-HCl, pH 7.5, 1 mM MgCl2, 0.25 M sucrose, 0.1 mM phenylmethylsulfonyl fluoride, 1 ig/ml chymostatin (Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure used for isolating MDBP and DNA methyltransferase from human placental nuclei involved previously described methods with some modifications (14,15). Two full-term placenta minus the chorionic plate were minced and homogenized for 10 sec at full speed in a Waring Blender and then in a Potter-Elvejehm homogenizer with six strokes at 3/4 maximum speed using 3-4 volumes of 50 mM Tris-HCl, pH 7.5, 1 mM MgCl2, 0.25 M sucrose, 0.1 mM phenylmethylsulfonyl fluoride, 1 ig/ml chymostatin (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…After a further 1:1 dilution with this buffer, the suspension was filtered through two layers of gauze, then through four layers, and lastly through a nylon membrane (HD3-70; Tetko, Depew, N.Y.). The filtrate was centrifuged and the crude nuclear pellet was rinsed, extracted with 0.3 M NaCl, and the extract centrifuged as previously described (14,15). The supernatant was diluted with 2.5 volumes of 25 mM potassium phosphate, pH 7.4, 0.1 mM EDTA, 0.2 mM dithiothreitol (DTT), 10% glycerol (buffer A) and applied at a flow rate of 80 ml/h to a phosphocellulose column (5 x 5 cm), which had been preequilibrated with buffer A plus 0.1 M KC1.…”
Section: Methodsmentioning
confidence: 99%
“…DNA reassociation experiments and subsequent restriction endonuclease analysis suggest that most CpG dinucleotides are symmetrically methylated (3). Purification of methylases from somatic nuclei and in vitro assays of their activities showed that in general, their preferred substrate was hemimethylated DNA (9,30). In addition, DNA-medi-ated gene transfer experiments showed that clonal inheritance of methylation patterns in vivo was restricted to the palindromic dinucleotide CpG (27).…”
mentioning
confidence: 99%
“…Eukaryotic DNA methyltransferase has been partially purified and characterized by several investigators (34,(43)(44)(45)(46). However, controversy still exists as to the existence of two distinct enzymes, since the de novo and maintenance methyltransferase activities do co-purify (26,44,46).…”
Section: Dna Methylation Patternsmentioning
confidence: 99%